The complete sequence of a human Y chromosome - Rhie, Arang; Nurk, Sergey; Cechova, Monika; Hoyt, Savannah J; Taylor, Dylan J; Altemose, Nicolas; Hook, Paul W; Koren, Sergey; Rautiainen, Mikko; Alexandrov, Ivan A; Allen, Jamie; Asri, Mobin; et al. (Nature, 2023)
The human Y chromosome has been notoriously difficult to sequence and assemble because of its complex repeat structure that includes long palindromes, tandem repeats and segmental duplications1-3. As a result, more than half of the Y chromosome is missing from the GRCh38 reference sequence and it remains the last human chromosome to be finished4,5. Here, the Telomere-to-Telomere (T2T) consortium presents the complete 62,460,029-base-pair sequence of a human Y chromosome from the HG002 genome (T2T-Y) that corrects multiple errors in GRCh38-Y and adds over 30 million base pairs of sequence to the reference, showing the complete ampliconic structures of gene families TSPY, DAZ and RBMY; 41 additional protein-coding genes, mostly from the TSPY family; and an alternating pattern of human satellite 1 and 3 blocks in the heterochromatic Yq12 region. We have combined T2T-Y with a previous assembly of the CHM13 genome4 and mapped available population variation, clinical variants and functional genomics data to produce a complete and comprehensive reference sequence for all 24 human chromosomes.
Keywords: telomery; referenční standardy; genomika; Chromosomes, Human, Y; satelitní DNA; heterochromatin; Genetics, Population; Genomics; Humans; Reference Standards; sekvence nukleotidů; multigenová rodina; Tandem Repeat Sequences; Heterochromatin; Sequence Analysis, DNA; genetická variace; segmentové duplikace; DNA, Satellite; Segmental Duplications, Genomic; tandemové repetitivní sekvence; Telomere; sekvenční analýza DNA; Multigene Family; Base Sequence; lidský chromozom Y; lidé; populační genetika; Genetic Variation